New Requirements for post-COVID-19 Hospital Inpatient Wards: Evidence, Design Recommendations and Assessment Tools - Nuvolari-Duodo, Isabella; Brambilla, Andrea; Ricciardi, Giovanni Emanuele; Dolcini, Michele; Capolongo, Stefano (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The evolution of hospital infrastructures highlights the need of its physical space to respond to new technological, societal and epidemiological transformations such as those following the COVID-19 pandemic experience. Although the new emerged needs of user-centeredness, comfort and wellbeing within specific functional areas, there is still a lack of measurable indications for addressing these challenges in-patient wards. Study Design. The objective of this study is therefore to provide specific guidelines for the design of the in-patient ward, through measurable criteria and indicators based on evidence from the scientific literature, and to develop an assessment tool for its evaluation. Methods. A five-step process has been followed: (i) performing a literature review about hospital wards and wellbeing strategies, (ii) conducting a best practice analysis and comparison of a selection of international contemporary healthcare facilities, (iii) defining some dimensional requirements from the comparison, (iv) developing an assessment tool based on extracted criteria, (v) testing the tool on an existing project. Results. Amongst the criteria, several aspects have been highlighted ranging from qualitative indicators, as the clarity of wayfinding or the level of privacy, to quantitative values, as the percentage of single inpatient rooms or the distance between rooms and nursing stations. The assessment tool is composed by 20 indicators, associated to thematic areas and referred to three environmental units of the inpatient ward. Two types of scoring system are proposed. Conclusions. Starting from those considerations and tool wider applications, the future design of hospital wards could follow guidelines addressing user-centeredness, comfort and wellbeing.